All new and all outcome-based? The German qualifications framework and the persistence of national governance approaches - Gössling, Bernd [Verfasser] (My University, 2016)
"This article analyses the development of the first national qualifications framework in Germany (Deutscher Qualifikationsrahmen or DQR). In this case, a qualifications framework, which is supposedly outcome-based, had to be adapted to a highly input-oriented qualification system. This raises the question, how clashing claims and governance approaches can be joined? The study draws upon the assumption that the discourse on the DQR development is driven by cognitive constructions of relevant policy-makers and that these mental constructions can be uncovered by an in-depth analysis of discourse-related paperwork, such as proposals and drafts, as well as transcripts of interviews with key actors. The analysis bears empirical evidence that many collectively shared patterns of interpretations remain stable, even in the face of a quite drastic impetus to change. This is especially the case for patterns linked to the persistent input-based paradigm of governance. Furthermore, new patterns of interpretations are revealed, which support the rising legitimacy of instruments in line with outcome-oriented governance. Arguments for outcome-based governance are, moreover, an integral part of the policy discourses around the DQR and might lead to nuances of change for new and overhauled qualifications in the future." (author's abstract; BIBB-Doku)
Keywords: S 2.2.4 Anrechnung, Prüfung & Zertifizierung; S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; Deutscher Qualifikationsrahmen; Lernergebnisorientierung; Governance; Bildungssteuerung; Berufsbildungspolitik; Diskursanalyse